Reading comprehension : what is it? how do you teach it? - Dymock, Susan J. (New Zealand Council for Educational Research, 1999)
An introduction to reading comprehension. Teaching about how narratives are written. Teaching about how expository texts are written. Answering questions about text. Sustained silent reading. Reading words faster can improve the comprehension of poor readers. Assessing reading comprehension. Some final comments.